De Garengeot's hernia with appendicitis—a rare cause of an acutely painful groin swelling. Issue 5 (16th May 2019) - O'Connor, Adam; Asaad, Peter
Abstract: De Garengeot hernia is a rare subtype of femoral hernia whereby the vermiform appendix is located within the hernial sac. Even rarer is the presence of appendicitis within the hernia sac. De Garengeot's hernia is difficult to diagnose pre-operatively and can prove technically difficult at operation particularly with regards to mobilization of the caecum and appendix in order to perform appendicectomy. Laparoscopic, open, with and without mesh repair of de Garengeot hernia have all been described in the literature with varying degrees of success. We present a case of an 82 year old lady presenting with an acutely painful right sided groin lump. CT scan revealed the presence of de Garengeot hernia with acute appendicitis. We describe in text and photo format our approach to the hernia repair, appendicectomy and provide a short review of the literature with regards to the different operative approaches to such a patient.